2018
DOI: 10.1002/tox.22632
|View full text |Cite
|
Sign up to set email alerts
|

Effects of novel brominated flame retardant TBBPA on human airway epithelial cell (A549) in vitro and proteome profiling

Abstract: The cellular toxicity response of human airway epithelial cells (A549) to tetrabromobisphenol (TBBPA) was assessed in vitro. Cell viability, levels of intracellular reactive oxygen species (ROS), lipid peroxidation (MDA), and caspase-3 activity were determined after A549 treated with varying concentrations of TBBPA. A comparative proteomic analysis was performed in cells treated with different concentrations of TBBPA (0, 10, and 40 μg/mL). Two-way anova analysis showed that cell viability was significantly dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 48 publications
(103 reference statements)
3
25
1
2
Order By: Relevance
“…TBBPA is a cytotoxicant that can interfere with cellular signaling pathways, reducing cell viability and proliferation . Previous studies demonstrated that the PBDEs including derivatives reduced cell viability in various cell lines . In agreement with these studies, we found that TBBPA at concentrations ranging from 8 to 64 μg·mL −1 significantly reduced the viability of BEAS‐2B cells at the time points of 12 h, 24 h, and 48 h. The decrease of cell viability treated by TBBPA was in agreement with those reported on other biphenyl organic pollutants.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…TBBPA is a cytotoxicant that can interfere with cellular signaling pathways, reducing cell viability and proliferation . Previous studies demonstrated that the PBDEs including derivatives reduced cell viability in various cell lines . In agreement with these studies, we found that TBBPA at concentrations ranging from 8 to 64 μg·mL −1 significantly reduced the viability of BEAS‐2B cells at the time points of 12 h, 24 h, and 48 h. The decrease of cell viability treated by TBBPA was in agreement with those reported on other biphenyl organic pollutants.…”
Section: Discussionsupporting
confidence: 91%
“…25 Previous studies demonstrated that the PBDEs including derivatives reduced cell viability in various cell lines. [37][38][39] In agreement with these studies, we found that TBBPA at concentrations ranging from 8 to 64 μgÁmL −1 significantly reduced the viability of BEAS-2B cells at the time points of 12 h, 24 h, and 48 h. The decrease of cell viability treated by TBBPA was in agreement with those reported on other biphenyl organic pollutants. For example, a dose-dependent decrease was observed on human vascular endothelial cells (HUVECs) exposed to mono-(2-ethyhexyl) tetrabromophthalate (TBMEHP) at several sublethal concentrations.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Malondialdehyde (MDA) was showed as nmol thiobarbituric acid‐reactive substance (TBARS) per mg protein. Total protein was assayed utilizing commercial BCA protein kit (Sangon, Shanghai, China) on the basis of the manufacturer's guidances …”
Section: Methodsmentioning
confidence: 99%